The Hebrew Bible manuscripts: a millennium - Attia, Élodie; Perrot, Antony (Supplements to the textual history of the Bible, 2022)
In The Hebrew Bible: A Millennium , scholars from different fields and dealing with different material sources are trying to consider the Hebrew Bible as a whole. The development of new databases and other technological tools have an increasing impact on research practices. By inviting doctoral students, young researchers, and established scholars to contribute, this interdisciplinary book showcases methods and perspectives which can support future scientific collaborations in the field of the Hebrew Bible. This edited volume gathers relevant research from Dead Sea Scrolls Studies, Cairo Genizah Studies, European Genizah Studies, and from Late Medieval Biblical Manuscript Studies